Biotensegrity of the Extracellular Matrix: Physiology, Dynamic Mechanical Balance, and Implications in Oncology and Mechanotherapy - Tadeo, Irene; Berbegall, Ana P.; Escudero, Luis M.; Álvaro, Tomás; Noguera, Rosa (Frontiers in Oncology, 2014)
Cells have the capacity to convert mechanical stimuli into chemical changes. This process is based on the tensegrity principle, a mechanism of tensional integrity. To date, this principle has been demonstrated to act in physiological processes such as mechanotransduction and mechanosensing at different scales (from cell sensing through integrins to molecular mechanical interventions or even localized massage). The process involves intra- and extracellular components, including the participation of extracellular matrix and microtubules that act as compression structures, and actin filaments, which act as tension structures. The nucleus itself has its own tensegrity system which is implicated in cell proliferation, differentiation and apoptosis. Despite present advances, only the tip of the iceberg has so far been uncovered regarding the role of extracellular matrix compounds in influencing biotensegrity in pathological processes. Groups of cells, together with the surrounding ground substance, are subject to different and specific forces which certainly influence biological processes. In this paper we review the current knowledge on the role of extracellular matrix elements in determining biotensegrity in malignant processes, and describe their implication in therapeutic response, resistance to chemo- and radiotherapy, and subsequent tumor progression. Original data based on the study of neuroblastic tumors will be provided.